Soft M-Algebras and Soft M-Ideals - Mohammed Shahab Hassan (Tikrit Journal of Pure Science, 2025)
In this paper, I start by introducing and going over the new M-algebra classes. Additionally, I present new classes of soft algebras, which I refer to as soft M-algebras. I next introduce and explore new ideas in soft M-algebras, like soft M-subalgberas and soft M-ideals, using our new connotations. I also presented the theorem of soft M-ideals and soft M-algebras.